Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.bonr.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Primary human osteoblasts with reduced alkaline phosphatase and matrix mineralization baseline capacity are responsive to extremely low frequency pulsed electromagnetic field exposure — Clinical implication possible

Abstract: For many years electromagnetic fields (EMFs) have been used clinically with various settings as an exogenous stimulation method to promote fracture healing. However, underlying mechanisms of action and EMF parameters responsible for certain effects remain unclear. Our aim was to investigate the influence of defined EMFs on human osteoblasts' and osteoclasts' viability and function. Primary human osteoblasts and osteoclasts were treated 3 times weekly for 21 days during their maturation process using the Somage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
89
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(101 citation statements)
references
References 38 publications
(58 reference statements)
12
89
0
Order By: Relevance
“…As was reported by Zhai et al [], PEMFs could significantly upregulate the expression of two markers of cell cycle progression ( Ccnd 1 and Ccne 1 ) at osteoblast proliferation stage and alkaline phosphatase marker of osteoblast differentiation. Stimulation of PEMFs with different parameters were confirmed in several studies to significantly upregulate the expression of two important transcription factors, Runx2 / cbfa1 [Komori, ; Tsai et al, ; Zhou et al, , ; Ehnert et al, ; Yan et al, ; Zhai et al, ] and osterix [Cheng et al, ; Ehnert et al, ; Yan et al, ] at both proliferation and differentiation stages, which were involved in the development of the osteoblastic lineage (Table ). In addition, PEMF exposure also significantly upregulated the expression of genes involved in bone matrix formation, which were comprised of type 1 collagen ( COL1 ) [Lin and Lin, ; Zhou et al, ; Yan et al, ; Zhai et al, ]; noncollagenous proteins including osteocalcin ( OC ) [Jansen et al, ; Zhai et al, ] and bone sialoprotein ( BSP ) [Jansen et al, ]; as well as growth factors including insulin‐like growth factors‐1 ( IGF‐1 ) [Esmail et al, ], TGF‐β [Jansen et al, ], and bone morphogenetic proteins ( BMPs ) [Jansen et al, ; Zhou et al, ; Lin et al, ; Yan et al, ].…”
Section: Mechanisms Of Pemfs In Pmopmentioning
confidence: 92%
See 1 more Smart Citation
“…As was reported by Zhai et al [], PEMFs could significantly upregulate the expression of two markers of cell cycle progression ( Ccnd 1 and Ccne 1 ) at osteoblast proliferation stage and alkaline phosphatase marker of osteoblast differentiation. Stimulation of PEMFs with different parameters were confirmed in several studies to significantly upregulate the expression of two important transcription factors, Runx2 / cbfa1 [Komori, ; Tsai et al, ; Zhou et al, , ; Ehnert et al, ; Yan et al, ; Zhai et al, ] and osterix [Cheng et al, ; Ehnert et al, ; Yan et al, ] at both proliferation and differentiation stages, which were involved in the development of the osteoblastic lineage (Table ). In addition, PEMF exposure also significantly upregulated the expression of genes involved in bone matrix formation, which were comprised of type 1 collagen ( COL1 ) [Lin and Lin, ; Zhou et al, ; Yan et al, ; Zhai et al, ]; noncollagenous proteins including osteocalcin ( OC ) [Jansen et al, ; Zhai et al, ] and bone sialoprotein ( BSP ) [Jansen et al, ]; as well as growth factors including insulin‐like growth factors‐1 ( IGF‐1 ) [Esmail et al, ], TGF‐β [Jansen et al, ], and bone morphogenetic proteins ( BMPs ) [Jansen et al, ; Zhou et al, ; Lin et al, ; Yan et al, ].…”
Section: Mechanisms Of Pemfs In Pmopmentioning
confidence: 92%
“…Furthermore, it was shown in that study that PEMFs with specific parameters could significantly improve osteoblast functions, which was evidenced by ALP staining and alizarin red staining. Meanwhile, Ehnert et al [2015] also discovered that extremely low-frequency PEMFs with specific parameters could partly result in remarkably improved mitochondrial activity, total protein content, alkaline phosphatase activity, and formation of mineralized matrix of human osteoblasts with poor initial osteoblast functions. However, effects of PEMFs on bone formation remained a source of controversy with a window effect, which was similar to findings in animal and clinical studies.…”
Section: Effects Of Pemfs On Bone Cellsmentioning
confidence: 99%
“…On the contrary, but possibly consistent with a proliferative phenotype, ALP activity and Osteocalcin expression were decreased in cultures exposed to PEMFs [Lin and Lin, ]. Increased resistance to oxidative stress was further investigated in a recent study by Ehnert et al [] using primary human osteoblasts (hOBs) exposed to 0.6 Hz, 0.28 mT PEMF bursts of 16 Hz pulses for 7 min/day, using a stimulation regime that was shown to be able to increase cell differentiation in the same cell model [Ehnert et al, ]. The authors demonstrated that EMFs induced the generation of Reactive Oxygen Species (ROS) in hOBs, most noticeably O 2 − (superoxide anion) and H 2 O 2 (hydrogen peroxide), and also induced the expression of antioxidant enzymes superoxide dismutase, catalase, glutathione peroxidase, and glutathione reductase.…”
Section: Effects Of Pemfs On Osteoblastsmentioning
confidence: 99%
“…Ehnert et al identified a specific extremely low-frequency pulsed electromagnetic field (ELFPEMF) (10 to 90.6 Hz) that supports human osteoblast function in an ERK1/2-dependent manner. The ELF-PEMF by producing non-toxic amounts of reactive oxygen species (ROS), induced antioxidative defense mechanisms in these cells [63, 64]. …”
Section: Physical Stimulation For Bone Regeneration and Fracture Healingmentioning
confidence: 99%